RANCANGAN SISTEM PENGENDALI SUHU DAN KELEMBABAN BERBASIS MIKROKONTROLER PADA RUANG PERTUMBUHAN FODDER (FODDER GROWTH CHAMBER) - Bambang Marhaenanto (Faculty of Agricultural Technology, University of Jember, 2021)
The availability of green feedstock for sheep is difficult to find during a dry season. To resolve this problem, seed seedlings such as sorghum and corn are known as green fodder is needed. In order to maintain seedling productivity, fodder planting is carried out in a chamber to control temperature, humidity, and light regulators. The objective of this study was to design a fodder growth chamber for providing sheep feed. The chamber is 4×3×3 m (l×w×h) which is equipped with a tray rack, evaporative cooler, humidifier, exhaust fan, and LED strip. A controller unit was employed to maintain temperature and humidity. The controller is based on a microcontroller that is programmed using BASCOM AVR. The controller unit was tested to maintain the temperature within the range of 35-45oC and humidity within 55-75%. It resulted a graph that indicated that temperature has fluctuated between desired range as well as humidity. Corn seeds were grown on the tray (700 g per tray) for 10 days and produced 1500 g per tray. Keywords: animal feed, automatic control, fodder microcontroller